The Influence Of Brand Love And Brand Trust On Repurchase Intention Through Consumer Satisfaction Of Indomie Products In Pekanbaru City - Kennedy, Nurul Fadilla; Wijayanto, Gatot; Nursanti, Aida (InJEBA : International Journal of Economics, Business and Accounting, 2024)
This study was conducted to determine the effect of Brand Love and Brand Trust on Repurchase Intention through Consumer Satisfaction of Indomie products in Pekanbaru City. The population in this study are consumers who know and have bought Indomie products. In sampling using nonprobability sampling with purposive sampling technique so that a sample of 114 respondents was obtained. The data analysis method uses Structural Equation Modeling (SEM) with the SmartPLS version 4 program. The results showed that Brand Love and Brand Trust affect the Consumer Satisfaction of Indomie products in Pekanbaru City. Brand Love and Brand Trust affect Repurchase Intention in Indomie products in Pekanbaru City. Consumer Satisfaction affects Repurchase Intention in Indomie products in Pekanbaru City. Brand Love and Brand Trust affect Repurchase Intention through Consumer Satisfaction of Indomie products in Pekanbaru City.